Do conditional cash transfers reduce household vulnerability? Evidence from PROGRESA-Oportunidades in the 2000s - Naoko Uchiyama (EconomiA, 2019)
A number of researchers and policymakers have revealed the short- and medium-term impacts of conditional cash transfer (CCT) programs; however, accumulation of full-scale evaluations of their long-term impact is ongoing. To contribute to filling the gap, this study empirically examines the vulnerability of rural households in Mexico and how CCT has recently impacted them. Using two Mexican rural household panel datasets from the 2000s, I adopt Kurosaki's (2006) version of Townsend's (1994) risk-sharing model with instrumental variable methods, which enables a greater focus on household welfare decline. The empirical results confirm that CCT played a certain role in reducing household vulnerability in the 2000s; however considering the situation after the global crisis in 2008 and the exact mechanism through which this occurs remains subject to further examination.
Keywords: O12; D12; O54; 330; Consumption smoothing; Household vulnerability; PROGRESA-Oportunities